EL FESTIVAL DE EUROVISIÓN: MÁS ALLÁ DE LA CANCIÓN - Laura ORTIZ MONTERO (Fonseca, Journal of Communication, 2023)
The European Broadcasting Union (EBU) was born in 1950 to improve service radio and television through collaboration and sharing content. This was, initially, limited only to news and sports. Therefore, in order not to be based only on that content, in 1956 they opted to create an event where music was a link between peoples: the Eurovision Song Contest. Sixty-one years later, the Song Contest has become one of the longest running programs in television in the world as well as one of the events that have the highest audience. The objective of this research is to know if the Eurovision Song Contest fulfills the purposes of the EBU, which refer to cultural diversity and the identity of peoples.